Antioxidant and Cytotoxic Activities of Isolated Compounds from Ethyl Acetate Fraction of Alpinia oxyphylla Fruits - Fan, Wei; Wang, Cheng-Zhong; Bao, Xiao-Li; Yuan, Hui-Hui; Lan, Min-Bo (Asian Journal of Chemistry, 2015)
A bioactivity-guided isolation and purification process was used to identify the antioxidant and cytotoxic components from the ethyl acetate fraction of Alpinia oxyphylla fruits. Four subfractions of the ethyl acetate fraction were obtained by a silica gel column chromatography eluted with petroleum ether-ethyl acetate, of which subfraction A showed the highest antioxidant and cytotoxic activities was selected for the isolation and identification of major active compounds. Seven compounds including nootkatone (1), tectochrysin (2), b-sitosterol (3), chrysin (4), protocatechuic acid (5), (4S*, 5E, 10R*)-7-oxo-tri-nor-eudesm-5-en-4b-ol (6) and (4R, 6R, 10S)-4,10-dimethyl-6-(1'-hydroxyisopropyl)-1-en-3,4,5,6,7,8-hexahydronaphthalen-2-one (7) were isolated. Compounds 6 and 7 were found firstly from this plant. Biological tests revealed that compounds 5, 6, 7 were the major antioxidant compounds and compounds 1, 3, 4, 5 exhibited potent cytotoxicity on different cancer cells, which probably responsible for the antioxidant and anticancer activities of the ethyl acetate fraction of Alpinia oxyphylla fruits.